2012
DOI: 10.4103/0300-1652.99830
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of peripheral intravascular catheters with biofilm producing microbes: Evaluation of risk factors

Abstract: Background:Biofilms often colonize catheters and contribute to catheter-related septicemia. However, predictors of catheter colonization by biofilms remain poorly defined. The aim of this study was to evaluate clinical factors that may be associated with biofilm colonization of catheters.Materials and Methods:A total of 54 isolates colonizing the peripheral intravascular catheters (IVCs) were studied and their biofilm production ability was analyzed by the tube method and antimicrobial susceptibility was also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…Current data provide evidence that the majority of Candida species recovered from the FOA (biomaterials) have higher capacity to produce biofilm. Similar results were obtained by other studies 45,46 . Kuhn et al, 37 reported that invasive C. albicans isolates form more biofilm than noninvasive isolates 37 .…”
Section: Discussionsupporting
confidence: 93%
“…Current data provide evidence that the majority of Candida species recovered from the FOA (biomaterials) have higher capacity to produce biofilm. Similar results were obtained by other studies 45,46 . Kuhn et al, 37 reported that invasive C. albicans isolates form more biofilm than noninvasive isolates 37 .…”
Section: Discussionsupporting
confidence: 93%
“…It has been demonstrated that there are some correlations between the biofilm-forming capacity of bacteria, and patient demographics and characteristics [ 24 – 26 ]. In the case of S epidermidis , previous studies found a significant correlation between the type of biological samples, and the biofilm production.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, this study detected a high capacity to form a biofilm (using the MTP method) which correlated with the hospital wards. However, other factors, such as gender, presence of invasive devices, and prior or prolonged hospitalization have also been shown to be associated with biofilm production by microbes [ 24 – 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon can have deleterious effects because biofilm formation is thought to play an important role in the survival of virulent strains of Staphylococci. In human medicine, it has been estimated that most of nosocomial infections are biofilm associated ( 14 ), Moreover, biofilm formation has been shown to be positively correlated with resistance to antimicrobial agents ( 15 ). About half (45%) of our biofilm producer isolates were also positive in beta -lactamase test.…”
Section: Discussionmentioning
confidence: 99%